2017
DOI: 10.1039/c6cp08852j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ion–ligand binding on ion pairing dynamics studied by two-dimensional infrared spectroscopy

Abstract: Cation-specific ion pairing dynamics between M (M = Ag or Cu) and SCN in N,N-dimethylthioformamide (DMTF) are studied by probing the nitrile (CN) stretching vibration. The SCN ion, which is an ambidentate ligand, readily associates with cations to form two different types of contact ion pairs (CIPs) (i.e., M-SCN or M-NCS) and its CN stretching frequency is significantly blue-shifted so that free SCN and CIPs can be well-distinguished in the FTIR spectra. Interestingly, Ag ions prefer the formation of Ag-SCN in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…As a result, they can vibrate in unison and thus form delocalized states, called vibrational excitons . Therefore, it is reasonable to assign the relatively small and broad peak centered at around 2150 cm –1 to the delocalized vibrational mode formed by CN stretching because it disappears in the FTIR spectrum of the CuSCN solution . The UV–vis spectrum of the CuSCN film on the CaF 2 substrate is shown in Figure C.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…As a result, they can vibrate in unison and thus form delocalized states, called vibrational excitons . Therefore, it is reasonable to assign the relatively small and broad peak centered at around 2150 cm –1 to the delocalized vibrational mode formed by CN stretching because it disappears in the FTIR spectrum of the CuSCN solution . The UV–vis spectrum of the CuSCN film on the CaF 2 substrate is shown in Figure C.…”
supporting
confidence: 93%
“…However, all of the SCN groups are parallel to each other in the CuSCN film, which is different from the case in the reverse micelle confined system. The distinct observation shown in Figure A indicated that the rotational dynamics of the CN stretching mode in the CuSCN semiconductor film should be very different from that observed in the CuSCN solution or the KSCN film …”
mentioning
confidence: 88%
See 2 more Smart Citations
“…We also observe that the free anion peak is located ∼2 cm –1 lower for the electrolyte with TMPE-OH than for the other electrolytes because of interactions between the anions and the hydroxyl end groups of the ion transporter, as previously reported for other hydrogen-bonding systems . We emphasize that the different ionic species detected with FTIR exist in a dynamic equilibrium and that the same ion can be expected to rapidly shift from being free to aggregated on a short time scale, as also indicated by the single 7 Li signal in the NMR experiments.…”
Section: Results and Discussionmentioning
confidence: 99%